Socioeconomic determinants of excess weight and obesity among Indigenous women: findings from the First National Survey of Indigenous People’s Health and Nutrition in Brazil - Coimbra, Carlos EA (Public Health Nutr, 2021)
OBJECTIVE: This article assesses the nutritional status of Indigenous women from 14 to 49 years of age in Brazil. DESIGN: Sample size was calculated for each region considering a prevalence of 50 % for all disease outcomes, a relative error of 5 % and a CI of 95 %. In the initial data analysis, the prevalence of excess weight and obesity was calculated according to independent variables. Multivariate multilevel hierarchical analyses were conducted based on a theoretical model of two ranked blocks. SETTING: The 2010 Indigenous population in Brazil was 896 000, with approximately 300 Indigenous ethnic groups, making Brazil one of the most ethnically diverse countries in the Americas and the world. PARTICIPANTS: Of the total target sample of 6722 women evaluated by the National Survey, thirty did not participate, 939 were not eligible for analyses due to pregnancy or unknown pregnancy status, and thirty-nine were excluded due to missing anthropometric data. RESULTS: The evaluation of nutritional status was completed for 5714 non-pregnant women (99·3 % of eligible participants for this outcome). High prevalence rates were encountered for both excess weight (46·2 %) and obesity (15·8 %) among the sampled women. In the multivariate analyses, higher socioeconomic indicators, market-integrated living conditions and less reliance on local food production, as well as increased age and parity were associated with excess weight and obesity. CONCLUSION: Results point to distinct patterns of associations between socioeconomic indicators and the occurrence of excess weight and obesity among Indigenous women, which have potentially significant implications from a public policy perspective for Indigenous peoples in Brazil.